PENGEMBANGAN MEDIA MONOPOLI BERBAHAN LOOSEPART UNTUK MENINGKATKAN KEMAMPUAN LOGIKA MATEMATIKA - Dian Fitri Argarini; Ifa Putri Wahyuhidayati (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
This research aims to determine the feasibility of the monopoly media "MAK (FUN MATHEMATICS" ROUND" made from loose parts for children aged 5-6 years. This research is research using research and development methods or what is called Research and Development (R&D) using a development model ADDIE. The subjects of this research were group A at Darul Hikmah Kindergarten, totaling 10 children consisting of 5 boys and 5 boys. women. In this study, media validation and observation validation of learning outcomes were carried out first by material experts and media experts, after that the validator produced an evaluation of the media and observation sheets used. The aim was to test the suitability of the media used. Research instruments used in the research This is an observation sheet that has been validated by experts. The indicators of the development of mathematical logic studied are knowing simple classifications, knowing numbers, knowing arithmetic operations, knowing geometric shapes. Learning media with the MAK ROUND monopoly game using loosepart media which was developed for group A2 children at DARUL HIKMAH Kindergarten has been validated by experts and received a percentage score of 92.72%. This shows that the MAK ROUND monopoly is declared worthy of being tested. Before being given treatment, the average acquisition of mathematical logic skills was below average, namely 66.8% and was declared incomplete. This means that children's mathematical logic is still low. After being given treatment, the average gain in mathematical logic skills in group A2 children increased to 84.7%. This shows that learning media using the MAK ROUND monopoly game is effective in improving mathematical logic skills in group A children aged 5-6 years.